Ulcer healing and mechanism(s) of action involved in the gastroprotective activity of fractions obtained from Syngonanthus arthrotrichus and Syngonanthus bisulcatus - Batista, Leônia Maria; Lima, Gedson Rodrigues de Morais; Almeida, Ana Beatriz Albino de; Magri, Luciana de Pietro; Calvo, Tamara Regina; Ferreira, Anderson Luiz; Pellizzon, Cláudia Helena [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Sano, Paulo Takeo; Brito, Alba Regina Monteiro Souza (BioMed Central LTD, 2015)
Syngonanthus arthrotrichus and Syngonanthus bisulcatus, currently known for Comanthera aciphylla (Bong.) L.R.Parra & Giul. and Comanthera bisulcata (Koern.) L.R. Parra & Giul, popularly known in Brazil as sempre-vivas, are plants from the family Eriocaulaceae. They are found in the states of Minas Gerais and Bahia. The species are known to be rich in flavonoids to which their gastroprotective activity has been attributed. In this research, experimental protocols were performed to elucidate the associated mechanisms of action. The activity was evaluated using induced gastric ulcer models (acetic acid and ethanol-induced gastric lesions in NEM or L-NAME pre-treated mice, and by ischemia/reperfusion). Antioxidant enzymes, serum somatostatin, and gastrin were also evaluated. In chronic gastric ulcers, a single daily oral dose of Sa-FRF or Sb-FRF (100 mg/kg body wt.) for 14 consecutive days accelerated ulcer healing to an extent similar to that seen with an equal dose of cimetidine. The pre-treatment of mice with NEM (N-ethylmaleimide) or L-NAME (N-nitro-L-arginine) abolished the protective activity of Sa-FRF, Sa-FDF, Sb-FDF and Sb-FRF or Sa-FRF and Sb-FRF, respectively, which indicates that antioxidant compounds and nitric oxide synthase activity are involved in the gastroprotective. Sa-FRF and Sb-FRF (100 mg/kg p.o) protected the gastric mucosa against ulceration that was induced by ischemia/reperfusion (72 and 76 %, respectively). It also decreased lipid peroxidation and restored total thiols in the gastric wall of mice that had been treated with ethanol. When administered to rats submitted to ethanol-induced gastric lesions, Sa-FRF and Sb-FRF (100 mg/kg, p.o.) increased the somatostatin serum levels, while the gastrin serum levels were proportionally decreased. The results indicate significant healing effects and gastroprotective activity for the Sa-FRF and Sb-FRF, which probably involves the participation of SH groups, nitric oxide (NO), the antioxidant system, somatostatin, and gastrin. All are integral parts of the gastrointestinal mucosa's cytoprotective mechanisms against aggressive factors.
Keywords: Eriocaulaceae; Syngonanthus arthrotrichus; Syngonanthus bisulcatus; Flavonoid; Healing; Gastroprotective activity